(3cJGH SjHhjgs - (3YeQh Hf YKeGf Hf bfHQ GdMGQKj, SjHhjg, CHh HTQ , J (B180 (3g` s
(3ChdgG (B:s
(3gPG HGH jchf ajg GdMQa GdPi ef faS GdGSe heG bHdg HefRdI RGFO hbY heG bHdg LejYkG , hPdc bhdc ai efUhQ (B: (3jG efU CbHd s
(3BNQgG (B:s
(3BNQg eHJhQ , jfJgi CKfGA (B" (3HGH eG jMPa ef GdCSeGA (B" (3Hbhd Wajd GdZfhi (B: (3Ef Gdbhi EP CfgG de jYjH s
(3GdfSNI HgG MhGTs
(3cJHJ YfhGfGJ GdCHhGH HGdNW Gdchais
(3hbO SbWJ GdCLRGA eG Hjf GdQGHY hGdKGef hai GdhQbI (B135 (3aUd djS ef GdcJGH hdcfg HNW GdfGSN faSg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B81 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B10s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs